Analisis Tingkat Pengetahuan, Sikap, Kebijakan dan Ketersediaan Sarana terhadap Perilaku Kepatuhan Menggunakan Alat Pelidng Diri (APD) pada Pengendara Go-Ride Dimasa Pandemi Covid-19 - Nadila Putri Rachmawati; Catur Yuantari (Faletehan Health Journal, 2022)
Go-Jek is an online-based service provider company. Unfortunately, Go-Ride drivers are one of the clusters for the spread of Covid-19 in Indonesia. This study analyzed the relationship between knowledge, attitudes, education, age, working period, availability of facilities, and legal regulations with compliance behavior of using personal protective equipment (PPE) during the Covid-19 pandemic era among online motorcycle taxi drivers in Tembalang area, Semarang City. The research method was quantitative with cross-sectional research design. The data collection was done by a questionnaire. The research samples were 100 drivers who were selected by using accidental sampling technique. The numerical data was analyzed by using statistical tests. The research results showed a relationship between attitudes and availability of facilities with compliance behavior of using PPE during Covid-19 pandemic era among online motorcycle taxi drivers in Tembalang area, Semarang City (p value 0.000 and 0.002). Online motorcycle taxi drivers were expected to further improve their compliance behavior of using PPE to prevent them from accidents and minimize the risk of severity in the event of an accident, and prevent from the transmission or spread of Covid-19 virus in the current pandemic era.